Mangrove Planting in Order to Increase the Carrying Capacity of Pond Land in Borimasunggu Village - Mulyani, Sri; Pallu, Muhammad Saleh; Mardiana, Mardiana; Fikruddin, Muhammad; Yunus, Muhammad Kafrawi; Fatmawati, Fatmawati; Handayani, Hainun Putri; Ningsi, Sitti Warda (International Journal of Public Devotion, 2024)
PT. Bosowa Isuma has a pond area of 157 ha and has been carrying out operational activities since 2010. Pond cultivation that is carried out continuously results in a decrease in land carrying capacity and will ultimately have an impact on the productivity of pond cultivation. The purpose of this activity is to maintain and improve the carrying capacity of pond land by planting mangroves along the river mouth of Borimasunggu Village. The implementation method is by conducting counseling and planting mangroves along the river mouth of Borimasunggu Village. The organizers of the activity were lecturers from the University of Bosowa, technicians from PT. Bosowa Isuma and 7 students of the MBKM Program. The result of the activity was counseling and planting of 500 Rhizopora apiculata mangrove seedlings along the river mouth of Borimasunggu Village. The resulting output is the planting of 500 Rhizopora apiculata mangrove seedlings along the river mouth of Borimasunggu Village, students gain sufficient knowledge and skills about planting mangrove plants and gain experience of 20 credits outside the campus and lecturers can carry out Tri dharma activities, namely carrying out community service. Mangrove planting can provide dual benefits both in terms of economy and environment, in the sense that production can increase and benefit farmers and the balance of the carrying capacity of pond land can be created/maintained.